Coupled thermo-hydro-mechanical computational modeling of an end bearing heat exchanger pile - Tran, Tri Van (Kansas State University, 2015)
Piles have been used for many years in civil infrastructure as foundations for buildings, bridges, and retaining walls. Energy piles are thermo-active foundation systems that use geothermal energy for heating and cooling of buildings. Ground source heat is a very attractive, economical, efficient and sustainable alternative to current heating practices. Unlike the air temperature, the temperature below the Earth’s surface remains relatively constant throughout the year, somewhere between 10oC to 15oC below a depth of 6 m to 9 m (Kelly, 2011). This provides an opportunity for construction of thermo-active foundation systems with embedded geothermal loops. The main purpose of such thermo-active system is to transfer deep ground heat to a building through the fluid circulating within the geothermal loop. It is because these thermo-active foundation systems enable heat exchange between the deep ground and the building that is called the heat exchanger pile (HEP). The thermal energy supplied by a HEP can then supplement air-pump-based heating/cooling system. Although heat exchanger piles have been successfully implemented in Europe and Asia, their usage in U.S. remains uncommon. One reason for this might be currently limited understanding of the associated soil-structure interaction, thus unfavorably affecting the design procedures. To this end, a study was undertaken to investigate the predictive capabilities of computational models and to gain a better understanding of the load-transfer mechanisms of energy piles. Thus, coupled thermo-hydro-mechanical computational modeling of a single actual end bearing HEP was carried out for different loading scenarios including thermal and mechanical loads by using the finite element code ABAQUS/Standard 6.13-2. The results of the analyses of the heat exchanger pile with two different types of layered soil profile are presented: isotropic and anisotropic. The computational model was validated and verified successfully against field test results for all considered loading scenarios. Additional analyses were performed to gain a deeper insight into the effects of soil layering and on the behavior of energy piles. It was found that changes in the soil stiffness affected primarily the head displacement and vertical stresses and strains in the pile.
Keywords: Energy pile; Load transfer mechanism; Numerical modelingHeat exchanger pile; Civil Engineering (0543)